2022
DOI: 10.1021/acs.energyfuels.2c01563
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Photocatalytic Memory Effect of Magneto-Plasmonic Ag–Fe3O4@TiO2 Ternary Nanocomposites for Dye Degradation and H2 Production under Light and Dark Conditions

Abstract: This study explores the preparation of Ag plasmons-sensitized magnetic-Fe 3 O 4 integrated TiO 2 (Ag−Fe 3 O 4 @TiO 2 ) ternary nanocomposites and their defectinduced electron storage properties to exploit their photocatalytic memory effect toward dye degradation and H 2 generation under light and dark conditions. The crystalline phase formation and elemental states of the individual materials and elements in the nanocomposite are analyzed using X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In the literature, the H 2 production via Ag plasmons‐sensitized magnetic‐Fe 3 O 4 integrated TiO 2 (Ag−Fe 3 O 4 @TiO 2 ) ternary nanocomposites was 911 μ mol/g.h under light conditions as seen in Table 2. However, this article used higher amounts of Ag particles (noble metal like Pt in our study) in their study which is the most probable reason for the high H 2 production rate [28] . Another study that uses Fe 3 O 4 and Co 3 O 4 doped TiO 2 indicated that Fe and Co ions together improved solar light absorption of TiO 2 , inhibited the recombination of photogenerated charges, and enhanced the photocatalytic activity of hydrogen production.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In the literature, the H 2 production via Ag plasmons‐sensitized magnetic‐Fe 3 O 4 integrated TiO 2 (Ag−Fe 3 O 4 @TiO 2 ) ternary nanocomposites was 911 μ mol/g.h under light conditions as seen in Table 2. However, this article used higher amounts of Ag particles (noble metal like Pt in our study) in their study which is the most probable reason for the high H 2 production rate [28] . Another study that uses Fe 3 O 4 and Co 3 O 4 doped TiO 2 indicated that Fe and Co ions together improved solar light absorption of TiO 2 , inhibited the recombination of photogenerated charges, and enhanced the photocatalytic activity of hydrogen production.…”
Section: Resultsmentioning
confidence: 80%
“…In another study, Ag plasmons‐sensitized magnetic‐Fe 3 O 4 integrated TiO 2 (Ag−Fe 3 O 4 @TiO 2 ) ternary nanocomposites were used for both dye degradation and H 2 generation under light and dark conditions. They observed red shift along with a distinct plasmonic band in the UV‐visible absorption spectrum due to metallic Ag nanoparticles, which was confirmed by the PL spectrum with an effective electron and hole separation [28] . Furthermore, mono‐ and co‐doped TiO 2 (Co n+ and Fe n+ ) were prepared by sol‐gel technique under solar light.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Chen and Shi presented a new approach to enhance photocatalytic oxidation of tetracycline by introducing boron nitride quantum dots to BiOBr with a permanent magnet to improve the charge carrier transfer . Venkatakrishnan and his co-workers reported a ternary composite consisting of TiO 2 , Fe 3 O 4 , and Ag that shows a photocatalytic memory effect toward dye degradation and H 2 production under light and dark conditions …”
Section: Photooxidationmentioning
confidence: 99%
“…30 Venkatakrishnan and his co-workers reported a ternary composite consisting of TiO 2 , Fe 3 O 4 , and Ag that shows a photocatalytic memory effect toward dye degradation and H 2 production under light and dark conditions. 31 ■ PHOTOREDUCTION There are eight papers on the topic of photoreduction. Yang et al reviewed the recent research progress and perspectives on porphyrin-based porous photocatalysts in CO 2 photoreduction.…”
Section: ■ Photooxidationmentioning
confidence: 99%